The Effect of Customer Trust, Lifestyle, and Attitude on the Online Buying Decision - S. Saparso (Quantitative Economics and Management Studies, 2022)
The internet is essential for business. It is because all people apply this connection to do their online activities, for example, buying. Therefore, many online platforms appear to facilitate it. The research about the decision to buy online and its determinants is numerous. In this study, three determinants want to get investigated: trust, lifestyle, and attitude. By employing the undergraduate management students in Universitas Kristen Krida Wacana as population and stratified random sampling as the method to take the samples, this study has the goal to examine these three effects on the decision to purchase online. Before testing the effect of trust, lifestyle, and attitude on the online buying decision, the data collected from the online survey get validated first by the confirmatory factor analysis. Then, the reliability test by the Cronbach Alpha analysis becomes the following step. Furthermore, after examining the statistical hypotheses by the structural equation based on variance, this study reveals that trust does not affect the online purchasing decision. However, lifestyle and attitude become the determinant with a positive sign. It implies that the platform has to be able to provide a safe transaction to raise the trust of the customer to buy online, the sellers have to assure the fits of products offered and delivery time promised.